Late Cretaceous volcanism and fluid circulation in the South Atlantic: Insights from continental carbonates in the onshore Namibe Basin (Angola). (December 2021) - Fiordalisi, E.; Marchegiano, M.; John, C.M.; Oxtoby, N.; Rochelle-Bates, N.; do Couto Pereira, G.; Machado, V.A.G.; Dixon, R.; Sharp, I.; Schröder, S.
Abstract: The Namibe Basin developed in the Early Cretaceous as part of the South Atlantic rift system between Africa and South America. Magmatic activity occurred during the syn-rift (Valanginian-Hauterivian) and post-rift (Coniacian-Early Campanian) phases, with the latter triggering fluid circulation events that had significant impacts on reservoir quality and hydrocarbon prospectivity. The continental carbonates of the Mariquita Member (Mb.) developed during the Late Cretaceous magmatic pulse and record the associated fluid circulation. Thus, study of these carbonates provides insights into paleo-fluid sources and circulation pathways, which can ultimately help to constrain diagenetic phases, their effects on reservoir quality, and hydrocarbon re-mobilisation. This study analyses the tectonostratigraphic setting, facies and diagenesis of the Mariquita Mb. carbonates by integrating field, petrographic and geochemical data. The carbonates are stratigraphically bound by Upper Cretaceous magmatic rocks, and constitute a series of fault-associated spring mound systems that pass laterally into lacustrine sediments. The main diagenetic events include pervasive dolomitisation, silicification and multi-stage fracturing. Fluid temperatures during dolomitisation were between ∼32 and 56 °C, while silicification occurred between ∼70 and > 260 °C. Fluids likely followed fault-controlled convective circulation pathways. The fluid compositions comprised infiltrated/modified meteoric and marine waters, as suggested by negative carbon isotopes, enriched oxygen and strontium isotopes, and REE data. Fluid modification occurred via interaction with subsurface rock units, such as basement, volcanic/siliciclastic aquifers and evaporites. However, higher temperatures during silicification could suggest late contributions from magmatic fluids too. Bitumen within porosity possibly reflects regional hydrocarbon mobilisation processes driven by magmatic fluids. Highlights: Spring mound and lacustrine carbonates formed during Late Cretaceous magmatic activity. Main diagenetic phases include pervasive dolomitisation, silicification and multi-stage fracturing. Magmatic activity initially acted as a source of heat for a convective fluid circulation fed by infiltrated waters. Fluids of magmatic origin possibly entered the plumbing system during a period of increased thermal regime.